Student Voices on the Roles of Instructors in Asynchronous Learning Environments in the 21st Century - Gómez-Rey, Pilar; Barbera, Elena; Fernández-Navarro, Francisco (International Review of Research in Open and Distributed Learning, 2017)
This paper determines which instructional roles and outputs are important in the 21st century from the perspective of students in asynchronous learning environments. This research work uses a literature review, in-depth interviews with experts, and a pilot study with students to define the instructors’ outputs. Following this, roles are determined by using a quantitative methodology (in a sample of 925 students). To our knowledge, the remaining research works on this topic identify the online instructors' roles by a qualitative analysis. The findings suggest that a new role, the life skill promoter, has emerged. Furthermore, analysis of the remaining roles (pedagogical, designer, social, technical and managerial) showed that: (i) online instructors are, first and foremost, pedagogues; (ii) the design of the particular online program influences the pedagogical and designer roles and; (iii) the managerial role has declined in importance over the years due to the development of more intuitive and transparent online scenarios from the beginning of the course onward.